2021
DOI: 10.3390/ijms222111408
|View full text |Cite
|
Sign up to set email alerts
|

NLRP2 Is Overexpressed in Spinal Astrocytes at the Peak of Mechanical Pain Sensitivity during Complete Freund Adjuvant-Induced Persistent Pain

Abstract: Our earlier findings revealed that interleukin-1 receptor type-1 (IL-1R1) was overexpressed in spinal neurons, and IL-1R1-deficient mice showed significant attenuation of thermal and mechanical allodynia during the course of the Complete Freund adjuvant (CFA)-induced persistent pain model. In the present study, we found that a ligand of IL-1R1, termed interleukin-1β (IL-1β), is also significantly overexpressed at the peak of mechanical pain sensitivity in the CFA-evoked pain model. Analysis of cellular distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Neuroinflammation and pain are tightly intertwined (Grace et al, 2014) and astrogliosis has a well-established role in other painful conditions. After complete spinal cord injury, increased GFAP persists for at least 3 weeks in the adult rat spinal cord (Choi et al, 2021;Ducza et al, 2021;Morin-Richaud et al, 1998;Nesic et al, 2006;Xu et al, 2021). However, the time course of the GFAP response to injury is different in neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroinflammation and pain are tightly intertwined (Grace et al, 2014) and astrogliosis has a well-established role in other painful conditions. After complete spinal cord injury, increased GFAP persists for at least 3 weeks in the adult rat spinal cord (Choi et al, 2021;Ducza et al, 2021;Morin-Richaud et al, 1998;Nesic et al, 2006;Xu et al, 2021). However, the time course of the GFAP response to injury is different in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes and microglia are activated by neural injury and release a plethora of pro-inflammatory molecules into the spinal milieu, and their activation corresponds to the development of neuropathic pain (Chhaya et al, 2018;Detloff et al, 2008;Gao et al, 2009;Hulsebosch et al, 2009;Ishikura et al, 2021;Lu et al, 2021;Xie et al, 2009;Zhang et al, 2016Zhang et al, , 2007. After complete spinal cord injury, increased GFAP persists for at least 3 weeks in the adult rat spinal cord (Choi et al, 2021;Ducza et al, 2021;Morin-Richaud et al, 1998;Nesic et al, 2006;Xu et al, 2021). However, the time course of the GFAP response to injury is different in neonates.…”
mentioning
confidence: 99%
“…For example, in the CFA-induced chronic inflammatory pain, the compound muscone, which diminishes ROS production, prevented the loss of mitochondrial membrane potential and Ca 2+ influx. Moreover, it blocked the CFA-induced increase in spinal cord NLRP3 and IL-1β expression and hyperalgesia (87,196). Importantly, the downstream product of inflammasome activation, IL-1β, induces firing of nociceptors and mediates CFA-induced pain (189,197,198), suggesting a putative role for NLRP3 inflammasome activation in inflammatory pain.…”
Section: Mitochondrial Mediated Nlrp3 Inflammasome Activationmentioning
confidence: 99%
“…It has been reported that pain-related clinical situations and experimental models are associated with inflammatory response activation in astrocytes ( Tan et al, 2021 ). Both NLRP2 and NLRP3 have been identified in spinal cord astrocytes during in situations of mechanical pain hypersensitivity in the complete Freund adjuvant-induced persistent pain model with IL-1β as effector and by activating the sphingosine-1-phosphate receptor ( Doyle et al, 2019 ; Ducza et al, 2021 ). It has been shown that the inflammatory activation in spinal cord astrocytes, and the associated pain, can be alleviated by treatment with the stilbenoid resveratrol ( Fan et al, 2021 ), and the molecular reduction of heat shock protein family A member 8 (HSPA8) ( Mi et al, 2021 ).…”
Section: Inflammasomes and Astrocytesmentioning
confidence: 99%